Quantitative, Non-Experimental Approaches to the Microeconomic Evaluation of Public Policy Measures - A Survey - Max Keilbach (Max Planck Institute of Economics, 2005)
The objective of evaluating public policy measures is to assess its implications and thus to obtain a measure for weather the respective program has been successful. In this paper, we consider and classify microeconomic and microeconometric approaches to measuring this success. To do so, the evaluation problem is outlined and three estimation priciples are presented. For each of these, underlying assumptions are identified and the consequences of their violation discussed.
Keywords: H43; O22; O38; O57; 330; Evuluation Methods; Public Policy Measures; Microeconometrics; Immaterialgüterrechte; Entrepreneurship-Ansatz; Selbstständige; Schätzung; Welt